Service Distribution in IP Networks – A Business Model Analysis - Wulf, Jochen (Electronic Communications of the EASST, 2011)
In this paper we analyze different business models for the distribution of content and services over IP networks and outline their distinct characteristics and value propositions. Four business models are distinguished: Centralized Internet Hosting, Direct Homing, Content Delivery Networks and P2P Distribution. In contrast to prior research, we focus on the ability of present technology to support distribution quality. Moreover, we discuss required value chain activities and roles, technological resources, as well as revenue models and cost structures. Following an inductive approach, we generalize from business models in practice. We present case studies in order to demonstrate, how these business models are implemented. This structured business model analysis demonstrates the different courses of action of providers regarding the IP based distribution of their content and services.